The Phytosterol Peniocerol Inhibits Cell Proliferation and Tumor Growth in a Colon Cancer Xenograft Model - Couder-García, Beatriz del Carmen; Jacobo-Herrera, Nadia J.; Zentella-Dehesa, Alejandro; Rocha-Zavaleta, Leticia; Tavarez-Santamaría, Zaira; Martínez-Vázquez, Mariano (Frontiers in Oncology, 2019)
Objective: This study aimed to evaluate the cytotoxic activity of peniocerol against human colon cancer cell lines and its antitumor effect in vivo in a xenograft model using nu/nu mice. Materials and Methods: SW-620, HCT-15, and HCT-116 colon cancer cell lines were treated with peniocerol for cytotoxicity by crystal violet technique. Cell apoptosis induction was detected by flow cytometry, and the antitumor activity of peniocerol was evaluated in a xenograft model of HCT-116 in nu/nu mice. After treatment, the effect of peniocerol was analyzed in histological sections of tumors by immunohistochemistry using DAPI, anti-PCNA, and PARP-1 antibodies. Results: Peniocerol inhibited cell growth and induced apoptosis in vitro in a time and dose-dependent manner. Besides, peniocerol administration (30 or 15 mg/kg) inhibited tumor growth and induced apoptosis in the xenograft mice. The lack of peniocerol toxicity was proved by a biochemical blood analysis of healthy nu/nu mice administrated with this sterol. Conclusions: Our results proved that peniocerol induces apoptosis in vitro and in vivo assays.